Gamifying the flipped classroom: how to motivate Chinese ESL learners?. Issue 5 (19th October 2020) - Ho, Janet
ABSTRACT: Flipped classrooms emphasise a learner-centred and results-oriented approach. They have been widely adopted in recent years, to enhance the effectiveness of student learning and encourage students to understand and apply new information. This approach is also regarded as a type of blended learning, given that tutors decide on the pre-class work, which is often characterised by online materials, and in-class time is devoted to collaborative tasks. This paper proposes teaching English narrative genres by combining digital drawing with active learning approaches – storymaking and storytelling. It also examines Hong Kong university students' perceptions of gamified flipped classrooms, as well as their understanding of the narrative concepts taught. Based on a combination of surveys, narrative writing scores, and focus group interviews, this study found that participants regarded the group-based game task as more effective than the group discussion task. The collaborative group-based game fostered a positive classroom atmosphere, served as a review session that allowed students to identify areas for improvement and prepare for the exit examination, and reduced their anxiety and reticence toward using English. These findings confirmed previous research findings that students' behavioural, cognitive, and motivational engagement could be enhanced through a gamified flipped classroom. Pedagogical implications for ESL teachers were also discussed.